Intraoperative Fluorescence Cerebral Angiography by Laser Surgical Microscopy: Comparison With Xenon Microscopy and Simultaneous Observation of Cerebral Blood Flow and Surrounding Structures. Issue 6 (12th June 2018) - Ito, Yuhei; Suzuki, Kyouichi; Ichikawa, Tsuyoshi; Watanabe, Yoichi; Sato, Taku; Sakuma, Jun; Saito, Kiyoshi
Abstract: BACKGROUND: Laser surgical microscopes should enable uniform illumination of the operative field, and require less luminous energy compared with existing xenon surgical microscopes. OBJECTIVE: To examine the utility of laser illumination in fluorescence cerebral angiography. METHODS: Fluorescein sodium (fluorescein) was used as a fluorescent dye. We first compared the clarity of cerebral blood flow images collected by fluorescence angiography between the laser illumination and xenon illumination methods. We then assessed use of the laser illuminator for simultaneous observation of blood flow and surrounding structures during fluorescence angiography. Furthermore, the study was designed to evaluate usefulness of the thus determined excitation light in clinical cases. RESULTS: Fluorescence angiography using blue light laser for excitation provided higher clarity and contrast blood flow images compared with using blue light generated from a xenon lamp. Further, illumination with excitation light consisting of a combination of 3 types of laser (higher level of blue light, no green light, and lower level of red light) enabled both blood flow and surrounding structures to be observed through the microscope directly by the surgeon. CONCLUSION: Laser-illuminated fluorescence angiography provides high clarity and contrast images of cerebral blood flow. Further, a laser providing strong blue light and weak red light for excitation light enables simultaneous visual observation of fluorescent blood flow and surrounding structures by the surgeon using a surgical microscope. Overall, these data suggest that laser surgical microscopes are useful for both ordinary operative manipulations and fluorescence angiography.